The Effect of Zinc Concentration on Bioaccumulation in Milkfish (Chanos chanos) Use of 65Zn as a Radioactive Tracer - Wahyono, I. B.; Muslim, M; Suseno, H.; Suryono, C. A. (Atom Indonesia, 2024)
Bioaccumulation studies of zinc (Zn) in milkfish (Chanos chanos) have been carried out in the laboratory using a 65Zn radiotracer. The research was conducted to determine the effect of Zn concentration on the ability of Chanos chanos to accumulate and release these contaminants. Zn absorption follows the single-compartment model, and experiments were carried out until stable conditions were achieved. The stages of research were biota collection, acclimatization, bioaccumulation, and elimination. Acclimatization was carried out for biota adaptation in the experimental environment. Bioaccumulation was carried out for 7 days by placing the biota in an aquarium filled with seawater added with 65Zn radiotracer contaminants. The elimination process involves the release of contaminants from the biota by placing them in contaminant-free seawater for 7 days. The results of the bioaccumulation experiment showed that the concentration factor (CF) ranged from 0.67 - 18.18 mLgr-1 at a concentration of ZnCl2 of 1.5 ppm, and the absorption constant (ku) 1.878 - 3.267d-1 and R2 was 0.0276. The release of contaminants in depuration experiments was highest at ZnCl2 2 ppm concentrations. The percentage of retention during depuration was between 14.61 - 79.91 %, the elimination constant (ke) was 8.681, and R2 was 0.7213.